Introduction: Perspectives on Cold War Science in Small European States. (11th August 2013) - Heymann, Matthias; Martin‐Nielsen, Janet
Abstract With this introduction we aim to illuminate Western Europe's place on the map of Cold War science and, specifically, to draw attention to the differences in and the diversity of Western European Cold War science in comparison to the United States. By discussing narratives of Cold War science in small states and asking how they fit into the European condition, we suggest that the fact of being a small state affects the conditions for and the scope of Cold War science. As a whole, this special issue also emphasizes the importance of the spatial dimension; that is, the significant dependence of Cold War science on geographical relations and geopolitical interests.